Contribution of the rvsp to the current crisis health (Revista Venezolana de Salud Pública, 2018)
Venezuela is going through a crisis that affects all sectors of National life. The health sector does not escape from it. The fragmentation of this system, where there are no clear guidelines for the ineffectiveness of the single health system, deepens the problems of the situation of care for patients and citizens who demand this service. Fiscal indiscipline collapses the financing of the sector and, together with galloping inflation, makes it increasingly difficult to provide adequate supplies and equipment in health institutions, both public and private.
Keywords: crisis; Health sector; Venezuela